PROMOTION OF MSMES "CASSAVA CHIPS JAJALON" MARKET THROUGH "SHOPEE": PROMOSI PENJUALAN UMKM “KERIPIK SINGKONG JAJALON” MELALUI MARKETPLACE “SHOPEE” - Yuliah Yuliah; Rika Kartika; Ade Fauji (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2021)
In today's digital age, e-commerce is often used in information technology, and one of the most commonly used e-commerce is the marketplace of the many marketplaces that often shopee. Currently, the marketing and results of MSMEs cassava chips jajalon still exist today. This method has not been optimal in information where it can not be coverage of the entire community. Which way to shopee with direct training to MSMEs for products, share and serve buying consumers. The result of the implementation of shopee access to MSMEs in the market and sales and sales to the top of the smartphone is the volume of sales.